4
$\begingroup$

How to integrate the following?

$$\int\frac{\sqrt{(1-x^2)^3}}{x^6} \;dx .$$

$\endgroup$
4
$\begingroup$

Let $x = \sin(\theta)$. We then get $dx = \cos(\theta) d \theta$. Hence, $$I= \int \frac{\cos^3(\theta)}{\sin^6(\theta)} \cos(\theta) d \theta = \int \cot^4(\theta) cosec^2(\theta) d \theta$$

Let $\cot(\theta) = t$, then $-cosec^2(\theta) d \theta = dt$. Hence, $$I = -\int t^4 dt = -\frac{t^5}{5} + c = -\frac{\cot^5(\theta)}{5} + c = -\frac15 \left( \frac{\sqrt{1-x^2}}{x} \right)^5 + c$$

$\endgroup$
3
  • $\begingroup$ +1: Your answer hadn't appeared yet when I was typing my comment. Or, at the very least, my eyes didn't see it. $\endgroup$ – J126 Oct 30 '11 at 16:18
  • $\begingroup$ There is a minor mistake out over there:If $t=cot\theta$ then $dt=-cosec^2\theta d\theta$ $\endgroup$ – Anamitra Palit Dec 4 '11 at 4:07
  • $\begingroup$ @AnamitraPalit: Thanks for pointing that out. $\endgroup$ – user17762 Dec 4 '11 at 5:54
3
$\begingroup$

Integral,

$$ \begin{align*} I &= \int \frac{\sqrt{(1-x^2)^{3}}}{x^6} dx \\ &= \int \left( \frac{1-x^2}{x^2} \right)^{3/2} \frac{1}{x^3}dx \\ &= \int \left(\frac{1}{x^2}-1 \right)^{3/2} \cdot \frac{1}{x^3} dx \end{align*} $$

Make the substitution: $z= \frac{1}{x^2}-1$, so that $dz=\frac{-2}{x^3} ~dx$.

$$ \begin{align*} \text{Integral} &= -\frac{1}{2}\int z^{3/2} dz \\ &= -\frac{1}{2} \cdot \frac{2}{5}z^{5/2}+C \\ &= -\frac{1}{5} \left(\frac{1}{x^2} - 1 \right)^{5/2}+C \\ &= - \frac{1}{5} \left(\frac{\sqrt{1-x^2}}{x} \right)^5+C. \end{align*} $$

$\endgroup$
2
$\begingroup$

Hint: Do the substitution $x = \sin(\alpha)$, $\alpha \in [-\frac{\pi}{2},\frac{\pi}{2}]$. Then you get $$\int \frac{\cos^4(\alpha)}{\sin^6(\alpha)} d\alpha.$$ Now consider the following identities: $$D\left(\frac{\cos^3(\alpha)}{\sin^5(\alpha)}\right) = \frac{-3\cos^2(\alpha)\sin^6(\alpha) - 5\sin^4(\alpha)\cos^4(\alpha)}{\sin^10(\alpha)} = -3\frac{\cos^2(\alpha)}{\sin^4(\alpha)} - 5 \frac{\cos^4(\alpha)}{\sin^6(\alpha)}$$ $$D\left(\frac{\cos(\alpha)}{\sin^3(\alpha)}\right) = \frac{-\sin^4(\alpha)-3\sin^2(\alpha)\cos^2(\alpha)}{\sin^6(\alpha)} = -\frac{1}{\sin^2(\alpha)} - 3 \frac{\cos^2(\alpha)}{\sin^4(\alpha)}$$

By using these it boils down to being able to integrate $\frac{1}{\sin^2(\alpha)}$.

$\endgroup$
2
  • $\begingroup$ Alternatively, you can rewrite $\frac{\cos^4(\alpha)}{\sin^6(\alpha)}$ as $\cot^4(\alpha)\csc^2(\alpha)$ and use a $u$-substitution for $u=\cot(\alpha)$, $du=-\csc^2(\alpha)\,d\alpha$. Then you need only integrate $-\int u^4\, du$. $\endgroup$ – J126 Oct 30 '11 at 16:14
  • $\begingroup$ @Joe Johnson 126: Yes, you're right. It seems to be what Sivaram Ambikasaran did in his answer. And it's simpler. $\endgroup$ – J. J. Oct 30 '11 at 17:43

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.